New Strains of Culex flavivirus Isolated in Argentina - Goenaga, Silvina (2014)
Strains of Culex flavivirus (CxFV), an insect virus isolated initially from Japan, were isolated from different species of Culex sp. mosquitoes collected in Corrientes province, Argentina, during 2009. CxFV was detected by reverse transcription polymerase chain reaction and by isolation in C6/36 cell culture. Phylogenetic analysis of nucleotide sequences showed that these strains are related closely to a CxFV strain isolated from Trinidad. Our study represents the first report of CxFV isolation and characterization in Argentina from the same geographic area where West Nile Virus has been detected. Further evaluation and viral competition studies will be necessary to determine the impact of this insect flavivirus on an infection caused by other pathogenic flaviviruses.